Margaret Fountaine (1862 – 1940). Skizzen aus dem abenteuerlichen Leben einer viktorianischen Schmetterlingsjägerin. - Eckl, Jürgen (Contributions to Entomology = Beiträge zur Entomologie, 2013)
Biographicalk scetch on the british entomologis Margaret Fountaine on base of excerpts of her diaries, which not before 38 years after her death in Trinidad 1940 were partially published. Descended from a pastoral household in the North Eastern Anglian province it was not perspective to convert a hobby into a lifetime compassion for entomology.She was promoted by the notorious. Collector Henry John Elwes. Due to heritage she was financially independent and capable to organize extensive excursions in Southern Europe, Middle East and North Africa, finally extensive collecting journeys in all continents in order of British and American museums and collectors. The Syrian Christ Khalil Neimy, fifteen years younger than the lady, became 1901 her permanent companion as butterfly hunter and her lover till his premature death in 1929. Since 1898 she was Member of the Royal Entomological Society (founded 1833) and was in the year 1912 invited to Membership of the Linnean Society of London (founded in 1788). After her death she bequeathed to the Castle Museum at Norwich a collection of 22.000 Diurnal Lepidoptera. Keywords British Entomologist, Victorian Heritance, World Wide Expeditions, Entomological results, Legacy